Comparison of digital platforms for participant recruitment in dementia research: Lessons and future directions from a global collaborative: Epidemiology / Innovative methods in epidemiology (i.e., assessment methods, design, recruitment strategies, statistical methods, etc.). (7th December 2020) - Jeon, Yun‐Hee; Fargo, Keith; Smith, Adam; Langbaum, Jessica B; Nosheny, Rachel L; Zwan, Marissa D; Shin, Mirim; Scheltens, Philip; Weiner, Michael W; Rossor, Martin N
Abstract: Background: Delays in finding the right research participants can result in studies taking longer to deliver, often requiring funding extensions and ultimately limit the effectiveness of research and evaluation when study samples are insufficient for robust analysis and generalisation of findings. Recruitment challenges in dementia research are a global issue. Method: To improve the effectiveness and efficiency of participant recruitment efforts in dementia research, innovative digital platforms have emerged over the past ten years: TrialMatch, Alzheimer's Prevention Registry & GeneMatch, and Brain Health Registry (USA), Join Dementia Research (UK), Hersenonderzoek (Netherlands), and StepUp for Dementia Research (Australia). Established in 2019, a global collaborative of these platforms aims to generate new insights and evidence that can help further enhance the service provision and potentially support other similar global initiatives. This paper provides an overview and comparison of the platforms, including key successes and challenges in their service delivery. Result: TrialMatch was the first platform developed to support recruitment processes in 2010. To date, collectively, the seven platforms have over 920, 000 volunteer members; >50% of them had opportunities to take part in studies as a result. The services are mostly free and rely on government grants and/or philanthropic funding for their delivery. They share common features (e.g., matching volunteer demographic and clinical information with studies) although some collect and use more detailed genetic and clinical profiles than others. Examination of the matching mechanisms and volunteer data access processes across the platforms suggests various opportunities to enhance the platforms. Key outcomes of these platforms also include a positive change in the way the public perceives dementia research and a systematic way for the public to engage in research. Understanding social and economic impact and ensuring sustainability of the platform and its service delivery are crucial steps for the future. Conclusion: The seven digital platforms have been showing their power and potential impact not only in fast‐tracking dementia research but also in improving public engagement and participation. Through this global partnership, the members share practices and strategies for sustainability of the programs that can contribute to the development of 'good' sustainable models for dementia research recruitment services.